A review on rear under-ride protection devices for trucks - Albahash Z.F.; Ansari M.N.M. (Taylor and Francis Ltd., 2023)
Accidents; Automobiles; Energy absorption; Finite element method; Trucks; Energy absorbing systems; Metal structures; Poor performance; Protection device; Rear side; Specific energy absorption; Structure design; Traffic safety; Crashworthiness